Changes in brain function during negative emotion processing in the long-term course of depression. (August 2022) - Enneking, Verena; Klug, Melissa; Borgers, Tiana; Dohm, Katharina; Grotegerd, Dominik; Frankenberger, Lisa Marie; Hülsmann, Carina; Lemke, Hannah; Meinert, Susanne; Leehr, Elisabeth J.; Opel, Nils; Goltermann, Janik; et al.
Abstract : Background: Relapses in major depression are frequent and are associated with a high burden of disease. Although short-term studies suggest a normalisation of depression-associated brain functional alterations directly after treatment, long-term investigations are sparse. Aims: To examine brain function during negative emotion processing in association with course of illness over a 2-year span. Method: In this prospective case–control study, 72 in-patients with current depression and 42 healthy controls were investigated during a negative emotional face processing paradigm, at baseline and after 2 years. According to their course of illness during the study interval, patients were divided into subgroups ( n = 25 no-relapse, n = 47 relapse). The differential changes in brain activity were investigated by a group × time analysis of covariance for the amygdala, hippocampus, insula and at whole-brain level. Results: A significant relapse × time interaction emerged within the amygdala ( P TFCE-FWE = 0.011), insula ( P TFCE-FWE = 0.001) and at the whole-brain level mainly in the temporal and prefrontal cortex ( P TFCE-FWE = 0.027), resulting from activity increases within the no-relapse group, whereas in the relapse group, activity decreased during the study interval. At baseline, the no-relapse group showed amygdala, hippocampus and insula hypoactivity compared with healthy controls and the relapse group. Conclusions: This study reveals course of illness-associated activity changes in emotion processing areas. Patients in full remission show a normalisation of their baseline hypo-responsiveness to the activation level of healthy controls after 2 years. Brain function during emotion processing could further serve as a potential predictive marker for future relapse.